Pengaruh Jenis Ransum Komersial pada Dua Strain Ayam Broiler terhadap Performa Ayam Broiler - Jumba, Paulus P. J.; Suryatni, Ni Putu F.; Sinlae, Markus; Mulyantini, N. G. A. (Yayasan Sumber Daya Manusia Cerdas, 2025)
This study aimed to evaluate the effects of three commercial feed types (P1, P2, P3) and two broiler chicken strains (A and B), as well as their interaction, on broiler growth performance. A 2x3 factorial Completely Randomized Design (CRD) was applied, using 96 broiler chickens divided into 6 treatment combinations with 4 replications. The observed parameters included body weight gain (BWG), feed consumption, feed conversion ratio (FCR), and final body weight. Data were analyzed using ANOVA with SPSS 25. The results indicated no significant interaction (P>0.05) between feed types and chicken strains on all measured parameters. The average BWG, feed consumption, FCR, and final body weight showed no significant differences among the treatments. In conclusion, the three commercial feeds and two chicken strains produced similar growth performance in 35-day-old broilers.